Parametric analyses of dynamic characteristic of the cable-stayed pedestrian bridże = Analizy parametryczne charakterystyk dynamicznych podwieszonej kładki dla pieszych - Pańtak, Marek; Jarek, Bogusław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents characteristics of the structural system and results of dynamic field tests and numerical parametric analyses of three-span, two-pylon, cable-stayed pedestrian bridge with steel-concrete composite deck and spans of 25.5 + 60.0 + 25.5 m.
Keywords: vibrations; footbridges; parametric analysis; cable-stayed bridges; dynamic characteristics; drgania; kładki dla pieszych; analiza parametryczna; charakterystyka dynamiczna